An Analysis of Customer Satisfaction and Loyalty of Online Transportation System in Pekanbaru, Indonesia. Issue 1 (March 2021) - Hamzah, M L; Purwati, A A; Jamal, A; Sutoyo,; Rizki, M
Abstract: This study aims to determine the mediating role of customer satisfaction in the relationship between customer trust and customer experience on customer loyalty in Grab transportation in Pekanbaru. The variables of this study include customer trust, customer experience, customer satisfaction, and customer loyalty. This research was conducted in Pekanbaru City. Data were collected through a questionnaire method which was filled independently of 400 respondents using the census / questionnaire method then analyzed by Structural Equation Modeling (SEM) with the help of SPSS 26.0 and Smart PLS 3.2.9. The results of the analysis prove (1) Customer Trust has a positive and significant effect on Customer Satisfaction, (2) Customer Experience has a positive and significant effect on Customer Satisfaction, (3) Customer Satisfaction has a positive and significant effect on Customer Loyalty, (4) Customer Trust has no effect and not significant to Customer Loyalty, (5) Customer Experience has a positive and significant effect on Customer Loyalty, (6) Customer Trust has a positive and significant effect on Customer Loyalty through the Customer Satisfaction variable, (7) Customer Experience has a positive and significant effect on Customer Loyalty through variables Customer satisfaction.